Estimating utility-consistent poverty in Ethiopia, 2000-11 - David Stifel; Tassew Woldehanna (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
We adapt the standardized Poverty Line Estimation Analytical Software (PLEASe) computer code stream based on Arndt and Simler's (2010) utility-consistent approach to analyse poverty in Ethiopia in 2000, 2005, and 2011. Several data-related issues create challenges to estimating the spatial and temporal distribution of poverty in a manner that meets both consistency and specificity objectives. This paper documents how we adapt the code stream to address changes in data collection periods and strata for the respective surveys over time. Changes in the duration and time of year for data collection can be especially problematic for consistency in the presence of annual inflation of over 30 per cent. In addition, the Ethiopia case provides an example of how to address convergence problems encountered when running the PLEASe code. Careful consolidation of spatial domains and limiting the number of iterations in the estimation of poverty lines are potential solutions.
Keywords: D63; I32; O55; 330; poverty measurement; utility-consistent poverty lines; inequality; Ethiopia